Directed aromatic functionalization in natural-product synthesis: Fredericamycin A, nothapodytine B, and topopyrones B and D - Turner, Charles Dylan; Ciufolini, Marco A. (Beilstein Journal of Organic Chemistry, 2011)
This is a review of our efforts toward the synthesis of a group of natural products that display noteworthy biological activity: Fredericamycin A, nothapodytine B, and topopyrones B and D. In each case, directed aromatic functionalization methodology greatly facilitated the assembly of the key molecular subunits.
Keywords: alkaloids; directed aromatic functionalization; fredericamycin; heterocyclic compounds; lithiation; nothapodytine; organolithium compounds; topopyrone